1906 Mass. Acts 150, ch. 172, An Act to Regulate by License the Carrying of Concealed Weapons § 2 - (:unkn) unknown (General Publisher, 1906)
Whoever, except as provided by the laws of this Commonwealth, carries on his person a loaded pistol or revolver, without authority or permission as provided in section one of this act, or whoever carries any stiletto, dagger, dirk-knife, slung-shot or metallic knuckles, shall upon conviction be punished by a fine of not less than ten nor more than one hundred dollars, or by imprisonment for a term not exceeding one year, or by both such fine and imprisonment.
--
Keywords: CARRY